2013
DOI: 10.3945/jn.113.175505
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Isoflavone Concentrations Are Not Associated with Gastric Cancer Risk among Japanese Men and Women1,2

Abstract: The incidence of gastric cancer throughout the world is ~2-3 times higher in men than in women. Previous research suggested that isoflavones, which are structurally similar to 17β-estradiol, may prevent gastric cancer. Based on a large, population-based, prospective study, we recently reported a null association between dietary isoflavone intake and gastric cancer. However, epidemiologic studies using blood concentrations of isoflavones might better reflect the effect of isoflavones on gastric cancer carcinoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…18): plasma isoflavone concentrations seemed to be maintained in Japanese who like isoflavone-rich foods. Our earlier work within the JPHC Study on the associations between isoflavones and cancers in other sites supports this assumption, with similar associations observed between the results of a cohort study using a food-frequency questionnaire and those of a nested casecontrol study using plasma concentrations (19)(20)(21)(22)(23)(24)(25)(26). Therefore, the present results indicate a possibility that plasma concentrations of isoflavones do not reflect dietary intake of isoflavones in people infected with hepatitis virus.…”
Section: Discussionsupporting
confidence: 72%
“…18): plasma isoflavone concentrations seemed to be maintained in Japanese who like isoflavone-rich foods. Our earlier work within the JPHC Study on the associations between isoflavones and cancers in other sites supports this assumption, with similar associations observed between the results of a cohort study using a food-frequency questionnaire and those of a nested casecontrol study using plasma concentrations (19)(20)(21)(22)(23)(24)(25)(26). Therefore, the present results indicate a possibility that plasma concentrations of isoflavones do not reflect dietary intake of isoflavones in people infected with hepatitis virus.…”
Section: Discussionsupporting
confidence: 72%
“…Studies among Western populations might not have detected significant associations due to the quite low intake of isoflavones among the majority of their participants (at most 10 mg/day), although estimates of nutrition intake should not be compared when calculated by different questionnaires. In addition, one nested case‐control study that measured plasma isoflavone concentrations observed associations between a decreased risk of stomach cancer and higher blood levels of isoflavone in Koreans, whereas another study of Japanese found no association . The inverse associations between soy isoflavone and stomach cancer should be further verified in different epidemiological studies.…”
Section: Discussionmentioning
confidence: 96%
“…The beneficial role of soybean products against gastric cancer remains debatable from an interventional point of view. A nested case-control study within the Korean Multicenter Cancer Cohort suggested that high serum concentrations of isoflavones were associated with a decreased risk of gastric cancer (115); on the contrary, a parallel nested case-control study within the Japan Public Health Center-Based Prospective Study indicated a null association between isoflavone intake and gastric cancer risk among Japanese men and women (116).…”
Section: Genistein and Cancermentioning
confidence: 99%